Influence of biodiesel fuel composition on the morphology and microstructure of particles emitted from diesel engines. (August 2016) - Savic, N.; Rahman, M.M.; Miljevic, B.; Saathoff, H.; Naumann, K.H.; Leisner, T.; Riches, J.; Gupta, B.; Motta, N.; Ristovski, Z.D.
Abstract: This study investigates the morphology, microstructure and surface composition of Diesel engine exhaust particles. The state of agglomeration, the primary particle size and the fractal dimension of exhaust particles from petroleum Diesel (petrodiesel) and biodiesel blends from microalgae, cotton seed and waste cooking oil were investigated by means of high resolution transmission electron microscopy. With primary particle diameters between 12 and 19 nm, biodiesel blend primary particles are found to be smaller than petrodiesel ones (21 ± 2 nm). Also it was found that soot agglomerates from biodiesels are more compact and spherical, as their fractal dimensions are higher, e.g. 2.2 ± 0.1 for 50% algae biodiesel compared to 1.7 ± 0.1 for petrodiesel. In addition, analysis of the chemical composition by means of x-ray photoelectron spectroscopy revealed an up to a factor of two increased oxygen content on the primary particle surface for biodiesel. The length, curvature and distance of graphene layers were measured showing a greater structural disorder for biodiesel with shorter fringes of higher tortuosity. This change in carbon chemistry may reflect the higher oxygen content of biofuels. Overall, it seems that the oxygen content in the fuels is the underlying reason for the observed morphological change in the resulting soot particles.